Hybrid knowledge and climate-resilient agriculture practices of the Tharu in the western Tarai, Nepal - Chaudhary, Buddhi R.; Erskine, William; Acciaioli, Greg (Frontiers in Political Science, 2022)
Indigenous knowledge can function as a basis of innovation in agriculture because it is not only culturally accepted, but often also environmentally adaptive. The debates and misunderstandings regarding the relations between Indigenous and scientific knowledge are transforming into a trend to integrate all knowledge to deal with complex issues, such as climate change. In this study we explore the understandings of the Tharu people of their farming system in relation to adaptation and mitigation of climate change, based on mixed methods design using both ethnographic analysis of their specific agriculture practices from participant observation and a survey of 229 households in the western Tarai of Nepal. Among our findings is the fit of the traditional agricultural calendar of the Tharu with the labor regimen of agricultural seasons. We found that conservation tillage-oriented agricultural practices, such as relay cropping, including zero-tillage, remain important in the farming system. Although this practice is decreasing, particularly due to the low yield as compared to the conventional tillage system, relay sowing and zero-tillage in the lowlands and uplands remain important for timely crop sowing. Similarly, mixed cropping is prevalent, particularly among small holders, for subsistence-based farming, in part due to higher yield than sole cropping. We conclude that Indigenous knowledge regarding climate and agriculture practices assists making informed decisions for climate-resilient and low emission agriculture. Although some traditional climate-resilient agriculture practices may yield lower profit than those derived from scientific knowledge/methods, the Tharu have therefore embraced “hybrid knowledge”—a combination of Indigenous and scientific knowledge, technology and practice—to balance increased yield and profit maximization with concurrent decreased vulnerability to extreme weather events. We argue that it is not useful to make firm distinctions among traditional, Indigenous and local knowledge in the age of hybridity. This hybridity is evident in the complementarity of the use of improved varieties and scientific agricultural practices for the major grains and the continuing use of landraces for minor crops such as lentils, peas and mustard. However, further research on the sustainable productivity of such practices is required before their widespread dissemination.